Food recognition application - Ke, Jiahao (Nanyang Technological University, 2021)
Singaporeans are facing health problems linking to obesity and type-2 diabetes. In a recent article in 2018, it is estimated that about 8.7% of Singaporeans adults face problems with obesity, while around 8.6% of Singaporeans had type-2 diabetes. It is projected that these numbers will continue to increase. One of the biggest reasons for the above is Singaporean overconsumption of unhealthy food [1]. Thus, there needs to be a solution to help Singaporean keep track of their daily ingestion of food and allow stronger awareness of healthier food alternatives. The objective of this project is to build a mobile application system that helps users keep track of their meals and encourage healthier diets. The application will allow users to take a photo of their meal using the application. The application will then recognize the type of food object(s) in the photo and feedback the user with information of each food object including the calories and nutrients. The user will be able to see a breakdown of the total consumption and nutrition values, compared to the recommended level according to the user’s portfolio